Lung‐Specific Risk Factors Associated With Incident Hip Fracture in Current and Former Smokers. (4th August 2020) - Bon, Jessica; Nouraie, Seyed Mehdi; Smith, Kenneth J; Dransfield, Mark T; McDonald, Merry‐Lynn; Hoffman, Eric A; Newell, John D; Comellas, Alejandro P; Saha, Punam K; Bowler, Russell P; Regan, Elizabeth A
ABSTRACT: Hip fractures are associated with significant morbidity and mortality in smokers with lung disease, but whether lung‐specific factors are associated with fracture risk is unknown. Our goal was to determine whether lung‐specific factors associate with incident hip fracture and improve risk discrimination of traditional fracture risk models in smokers. The analysis consisted of a convenience sample of 9187 current and former smokers (58, 477 participant follow‐up years) participating in the Genetic Epidemiology of chronic obstructive pulmonary disease (COPD) longitudinal observational cohort study. Participants were enrolled between 2008 and 2011 with follow‐up data collection through July 2018. Traditional risk factors associated with incident hip fracture ( n = 361) included age, female sex, osteoporosis, prevalent spine and hip fracture, rheumatoid arthritis, and diabetes. Lung‐specific risk factors included post‐bronchodilator percent forced expiratory volume in 1 s (FEV1 %) predicted (OR, 0.95; 95% CI, 0.92–0.99 for each 10% increase), Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification (OR, 1.09; 95% CI, 1.002–1.19 for each higher stage), presence of CT‐determined emphysema (OR, 1.34; 95% CI, 1.06–1.69), symptom scores (OR, 1.10; 95% CI, 1.03–1.19 for each higher unit score), 6‐min walk distance (OR, 0.92; 95% CI, 0.90–0.95 for each 30‐m increase), body mass index, airflow obstruction, dyspnea, and exercise (BODE) index (OR, 1.07; 95% CI, 1.01–1.13 for each higher unit score), total exacerbations (OR, 1.13; 95% CI, 1.10–1.16 per exacerbation), and annual exacerbations (OR, 1.37; 95% CI, 1.21–1.55 per exacerbation). In multivariable modeling, age, black race, osteoporosis, prevalent hip and spine fracture, rheumatoid arthritis, and diabetes were associated with incident hip fracture. The presence of emphysema, 6‐min walk distance, and total number of exacerbations added to traditional models improved risk discrimination (integrated discrimination improvement [IDI] values 0.001 [95% CI, 0.0003–0.002], 0.001 [95% CI, 0.0001–0.002], and 0.008 [95% CI, 0.003–0.013], corresponding to relative IDIs of 12.8%, 6.3%, and 34.6%, respectively). These findings suggest that the incorporation of lung‐specific risk factors into fracture risk assessment tools may more accurately predict fracture risk in smokers. © 2020 American Society for Bone and Mineral Research.